The Factors Related to Learning Habits of Mathayomsuksa 3 Students - Bunchoo, Monmanat; Srihaset, Kamontip; Tippayakulpairoj, Duranee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Learning habits are the behaviors expressed by students. To respond to learning which comes from learning, practicing, or practicing until it becomes a habit that affects the learning achievement of the students. Therefore, to obtain information that can be useful in determining guidelines for promoting and developing students ' good Learning habits was brought to this research. Therefore, this research has the objectives to 1) factors correlating with the learning habits of Matthayom Sueksa Three students and 2) create an equation to predict the learning habits of a sample group of Matthayomsueksa 3 students. Methodology: There were 264 Matthayomsueksa 3 students, which were obtained from cluster random sampling. Data was collected using a Questionnaire on factors related to the learning habits of Mathayom 3 students. The data was analyzed using multiple regression analysis. Results: (1) Learning habits with attitude in learning motivation to study Anxiety in studying The role of parents, the role of teachers, and the school environment. There is a correlation coefficient (R) equal to 0.58. The set of independent variables can explain 31.80 percent of the variance in the dependent variable (Adjusted R2). (2) The independent variable that has the greatest relationship with the learning habits of Mathayom 3 students was study attitude (b = 0.47), followed by the role of parents (b = 0.15) and study motivation (b = 0.14), respectively, by the factor prediction equation that has a relationship with learning habits of Mathayom 3 students by selecting variables into the equation using Enter method found that the regression coefficient (b) of study attitude, study motivation and the role of parents were statistically significant at the 0.05 level. The relationship could be written in a prediction equation in the raw score as follows: Learning habits = 0.50 + 0.52study attitude* + 0.07study motivation * + 0.13the role of parents * Conclusion: The results suggest that learning habits among Mathayom 3 students are significantly influenced by study attitude, parental involvement, and study motivation, with study attitude showing the strongest relationship. These factors collectively explain 31.80% of the variance in learning habits, highlighting the importance of positive attitudes towards studying and parental support in fostering effective learning behaviors.